Market power and journalistic quality - Martin Leroch (European Journal of Law and Economics, 2021)
The political news media play an important role in the successful working of democratic societies. In order to fulfill this role, a sufficient level of journalistic quality is required. Most Western societies rely on the market as means to assure this level of quality. This implies regulation of the media sector by competition law, which may take different attitudes towards market power. While it is undisputed that some aspects of competition between political news media firms yield beneficial social outcomes, empirical findings regarding the impact of changes in market power are less straightforward. In the present analysis, I aim to understand whether an increase in market power may lead to an increase in journalistic quality. To this end,I formally model a demand function for media outlets based on the empirically justified assumption that preferences for journalistic quality systematically differ among consumers according to their education. I refer to this finding as consumption capital in a wide sense. Using a model of monopolistic competition, I find that, if consumption capital is sufficiently high, an increase in market power is associated with an increase in journalistic quality.
Keywords: K20; L10; L82; 340; Journalistic quality; Political news market; Monopolistic competition